Pemanfaatan AI dalam Pembelajaran Bahasa Indonesia Berbasis Konteks Urban Farming: Studi Kasus Mahasiswa STIE Balikpapan - Putri, Fazila Aulia; Putri, Gracia Christiani; Juniyani, Lusi Asri; anhar, Anhar (Indo-MathEdu Intellectuals Journal, 2025)
This study examines strategies for utilizing Artificial Intelligence (AI) in Indonesian language learning by integrating urban farming contexts as contextual learning media. The research focuses on analyzing adaptive learning systems, educational chatbots, and automatic text analysis to enhance language learning quality. The research method employs a systematic literature review analyzing academic sources related to AI implementation in language education and urban farming as a meaningful learning medium. Results indicate that AI implementation significantly improves students' literacy skills, writing competencies, and contextual understanding. Urban farming as a learning context proves effective in enhancing learning engagement and connecting theory with real-world practices in contemporary socio-environmental issues. The integration of AI with urban farming creates meaningful and applicable learning experiences, preparing students to face digital-era communication challenges. This study recommends developing AI-based learning models that integrate real-world contexts to create more holistic and relevant learning experiences for the digital age.